A Randomized, Double-Blind, Placebo-Controlled Study to Assess the Efficacy and Safety of Ambroxol Hard-Boiled Lozenges in Patients with Acute Pharyngitis - Sousa, Rita (Pulm Ther, 2019)
INTRODUCTION: The aim of this study was to evaluate the efficacy and safety of a new hard-boiled lozenge formulation containing ambroxol 20 mg versus placebo for the relief of sore throat in patients with acute pharyngitis. METHODS: This was a phase 3, randomized, double-blind, placebo-controlled, parallel-group multicenter trial conducted between June and September 2018 in South Africa. Patients with a diagnosis of acute pharyngitis, onset ≤ 72 h, and sore throat pain of at least moderate intensity were randomized to receive either ambroxol 20 mg or placebo hard-boiled lozenges. The primary efficacy endpoint was the normalized time-weighted sum of pain intensity differences (SPID) from baseline over 3 h following administration of the first lozenge (SPID(norm,0–3h)). Secondary efficacy endpoints included SPID 24 h after the first lozenge intake (SPID(norm,0–24h)) and patient assessment of efficacy at 3 and 24 h after the first lozenge. RESULTS: Of 422 patients from 11 centers, 390 were randomized to one of the two treatment groups (n = 196, ambroxol; n = 194, placebo) and 388 were analyzed (modified intention-to-treat). The mean ± standard deviation SPID(norm,0–3h) values were −0.386 (0.259) and −0.366 (0.243) in the ambroxol and placebo groups, respectively, and the adjusted mean ± standard error SPID(norm0–3h) difference between ambroxol and placebo was −0.020 (0.025) (p = 0.443). Comparable results between treatment groups were also found for SPID(norm,0–24h) and patient assessment of efficacy at 3 and 24 h after the first lozenge. The incidence of treatment-emergent adverse events (TEAEs) was similar between treatment groups (11.7% for ambroxol versus 9.3% for placebo). CONCLUSION: Although marked pain relief was observed over the first 3 h of treatment, superiority of ambroxol 20 mg hard-boiled lozenges versus placebo was not demonstrated in this study. TRIAL REGISTRATION: NCT03583658. FUNDING: Sanofi-Aventis Group. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s41030-019-00100-w) contains supplementary material, which is available to authorized users.